PTSD as an Endothelial Disease: Insights From COVID-19 - Sfera, Adonis; Osorio, Carolina; Rahman, Leah; Zapata-Martín del Campo, Carlos Manuel; Maldonado, Jose Campo; Jafri, Nyla; Cummings, Michael Allen; Maurer, Steve; Kozlakidis, Zisis (Frontiers in Cellular Neuroscience, 2021)
SARS-CoV-2 virus, the etiologic agent of COVID-19, has affected almost every aspect of human life, precipitating stress-related pathology in vulnerable individuals. As the prevalence rate of posttraumatic stress disorder in pandemic survivors exceeds that of the general and special populations, the virus may predispose to this disorder by directly interfering with the stress-processing pathways. The SARS-CoV-2 interactome has identified several antigens that may disrupt the blood-brain-barrier by inducing premature senescence in many cell types, including the cerebral endothelial cells. This enables the stress molecules, including angiotensin II, endothelin-1 and plasminogen activator inhibitor 1, to aberrantly activate the amygdala, hippocampus, and medial prefrontal cortex, increasing the vulnerability to stress related disorders. This is supported by observing the beneficial effects of angiotensin receptor blockers and angiotensin converting enzyme inhibitors in both posttraumatic stress disorder and SARS-CoV-2 critical illness. In this review article, we take a closer look at the virus-host dialogue and its impact on the renin-angiotensin system, mitochondrial fitness, and brain-derived neurotrophic factor. In other words, learning from the virus, clarify the molecular underpinnings of stress related disorders, and design better therapies for these conditions. We also discuss new potential treatments, including furin and bromodomains inhibitors.